Author Correction: Comparison of eight complete chloroplast genomes of the endangered Aquilaria tree species (Thymelaeaceae) and their phylogenetic relationships - Muhammad Syahmi Hishamuddin (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.